2017
DOI: 10.1055/s-0043-119225
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Lower Leg Chronic Exertional Compartment Syndrome in a Large Population

Abstract: Knowledge about lower leg chronic exertional compartment syndrome (CECS) is largely obtained from highly selected populations. Patient characteristics may therefore not be appropriate for the general population. Our purpose was to describe a heterogeneous population of individuals suspected of lower leg CECS and to identify predictors of CECS. Charts of individuals who were analyzed for exercise-induced lower leg pain in a referral center between 2001 and 2013 were retrospectively studied. Patients were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 35 publications
0
59
0
4
Order By: Relevance
“…Some authors suggested that CECS may develop early during the athlete's sports career [14,15]. The level of practice may also influence the risk of CECS in Nordic skiers, elite skiers being more likely to develop CECS [16,17,19].…”
Section: Features Of Chronic Exertional Compartmental Syndrome Of Thementioning
confidence: 99%
See 3 more Smart Citations
“…Some authors suggested that CECS may develop early during the athlete's sports career [14,15]. The level of practice may also influence the risk of CECS in Nordic skiers, elite skiers being more likely to develop CECS [16,17,19].…”
Section: Features Of Chronic Exertional Compartmental Syndrome Of Thementioning
confidence: 99%
“…This value is relatively similar to the prevalence measured in the present study, but it could be overestimated since these authors based their diagnosis of CECS on symptoms only. Indeed, De Bruijn et al [14] showed that about 50 % of patients who had leg pain had normal intra-compartmental pressure. Waterman et al [24] measured the incidence of CECS in a military population between 2006 and 2011.…”
Section: High Cecs Prevalence and Incidence In Elite Nordic Skiersmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the incidence of CECS in general populations nowadays is increasing. A recent study in an ELP referral center found that one in eight individuals with CECS was a civilian over 50 years of age [4]. This trend of higher incidences of ELP in general populations is likely due to the 'exercise is medicine' movement that is currently embraced by large groups of active senior persons having sufficient spare leisure time.…”
Section: Cecs Conversely Soccer Players Withmentioning
confidence: 99%